Corrosion protection of steel structure for industrial application - Asmerol, Alias (2009)
The present paper discusses the study of effect of corrosion protection on steel structure, effect of PH medium on steel structure and effect of deformation on corrosion rate in order to find the best solution for the corrosion problem. The objective of this is to experiment and analyze the corrosion behaviour of steel structure, to investigate the effect of corrosion protection for industrial application and to analyze the effectiveness of corrosion protections in various medium. The thesis use mild steel as the specimen and 3 medium as for the type of environment which is acid, air and alkali. The thesis presents the effectiveness of protection between cathodic protections, coating and controlled specimen as default data. The sample preparation based on ASTM guide which involving specimen cutting, specimen deformation and specimen cleaning. Specimen deformation is the step where the specimen is bended 90° at the centre of specimen. The experiment is steps where the protection applied to specimen and expose to mediums for 28 days. The analysis step start from surface analysis using SEM to specimen cleaning using reagent and weight losses measurement at the end. From the result, it is observed that cathodic protection has the lowest corrosion rate compare to coating although there’s no big differences between them and acid medium has the recorded the highest corrosion rate while alkali medium recorded the lowest corrosion rate. The obtained result indicate that acidic medium tend to increase the corrosion rate while alkaline medium tend to decrease the corrosion rate. Although cathodic protection has the best result but the coating protection chosen the best protection due the limitation that cathodic protection can be applied. Nevertheless there are some recommendation to improve the quality of protection and its environment thus corrosion reaction can be avoided.